A critical comparison of smooth and sharp interface methods for phase transition. (November 2019) - Rajkotwala, A.H.; Panda, A.; Peters, E.A.J.F.; Baltussen, M.W.; van der Geld, C.W.M.; Kuerten, J.G.M.; Kuipers, J.A.M.
Highlights: A Local Front Reconstruction Method (LFRM) is extended to allow simulation of boiling flows. Mathematical formulation and implementation of two different approaches to treat energy equation are described. Both approaches are verified using 1D and 3D test cases and validated with experimental results of growth of rising bubble Comparison of results show advantages of sharp interface approach over smooth interface approach. Better accuracy and convergence rate, reduced velocity fluctuations and physically bounded temperature fields are observed for sharp interface approach. Abstract: In this study, the Local Front Reconstruction Method (LFRM) is extended to allow for the direct numerical simulation of flows with phase transition. The LFRM is a hybrid front tracking method without connectivity, which can easily handle complex topological changes. The expansion due to phase change is incorporated as a non-zero divergence condition at the interface. The energy equation is treated with two different approaches: smooth interface approach and sharp interface approach. The smooth interface approach uses a one fluid formulation to solve the energy equation with an interfacial source term accounting for phase change. This interfacial source term enforces the saturation temperature at the interface. However, in the sharp interface approach, the thermal properties are not volume-averaged near the interface and the saturation temperature is imposed as a boundary condition at the interface. A detailed mathematical formulation and numerical implementation pertaining to both approaches is presented. Both implementations are verified using 1D and 3D test cases and produce a good match with analytical solutions. A comparison of results highlights certain advantages of the sharp interface approach over the smooth interface approach such as better accuracy and convergence rate, reduced fluctuations in the velocity field and a physically bounded temperature field near the interface. Finally, both approaches are validated with a 3D simulation of the rise and growth of a vapor bubble in a superheated liquid under gravity, where a good agreement with experimental data is observed for the bubble growth rate.